The influence of Paternalistic leadership on the commitment and job satisfaction of the employees – A field study from the point of view of female administrators in academic departments at King Abdulaziz University in Jeddah – - Assas, Suha Fuad (Journal of Economic, Administrative and Legal Sciences, 2021)
The problem statement of this study is to check the influence of paternalistic leadership on the commitment and job satisfaction from the point of view of female administrators in academic departments at King Abdulaziz University.The aim of this study to contribute to increase the attention for the researchers to apply paternalistic leadership style, open the way for new studies, and help officials of academic departments in Saudi universities to upgrade the quality of the performance of the services provided by their subordinates through applying the paternalistic leadership style in their departments.The population of the study of female administrators in academic departments at King Abdulaziz University and a number of approximately 700 employees, the study sample was selected at random which has been adopted (63) The identification of origin (78). It has been used descriptive analytical method. And to analyze and manipulate data using a statistical computer program (SPSS).After the study data statistically analyzed the results showed that managers dealing with their employees by using paternalistic leadership style. In addition, there is a positive relationship between paternalistic leadership style and commitment of the employees. Although the leader was sometimes resorted to the use of authoritarian paternalistic leadership style, but the results showed that there is a functional commitment to the organization by the study sample. Also, there is a positive relationship between paternalistic leadership style and job satisfaction for the employees, even if the managers deal with their employees by using authoritarian paternalistic leadership style.In light of the results, researcher reached to a number of recommendations which is the most important one there is a need to apply the paternalistic leadership style by managers as it imparts the positive side on the commitment and job satisfaction of the employees.Finally, the researcher recommends to conduct more research in the paternalistic leadership style from the point of view of male administrators in academic departments at King Abdulaziz University, and comparing the results with the present study to determine the influence of Paternalistic leadership on the commitment and job satisfaction of the employees in the point of view of male and female employees.
Keywords: patriarchal leadership; commitment and job satisfaction; administrative employees in academic departments; King Abdulaziz University